2022
DOI: 10.3390/e24020176
|View full text |Cite
|
Sign up to set email alerts
|

Information Hiding in the DICOM Message Service and Upper Layer Service with Entropy-Based Detection

Abstract: The DICOM (Digital Imaging and COmmunication in Medicine) standard provides a framework for a diagnostically-accurate representation, processing, transfer, storage and display of medical imaging data. Information hiding in DICOM is currently limited to the application of digital media steganography and watermarking techniques on the media parts of DICOM files, as well as text steganographic techniques for embedding information in metadata of DICOM files. To improve the overall security of the DICOM standard, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Mantri et al [37] conducted a comparative study of DICOM API libraries, while NIST [38] identified software and managed risks within the PACS ecosystem. Mileva et al [39] introduced covert channels for DICOM transport mechanisms, offering possibilities for covert communications, data exfiltration, and privacy leaking attacks.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Mantri et al [37] conducted a comparative study of DICOM API libraries, while NIST [38] identified software and managed risks within the PACS ecosystem. Mileva et al [39] introduced covert channels for DICOM transport mechanisms, offering possibilities for covert communications, data exfiltration, and privacy leaking attacks.…”
Section: Related Workmentioning
confidence: 99%
“…In this research, Pydicom [46] was used as a tool to read DICOM files and send them to the Application Entity (AE). The AE supports Presentation Contexts, which consist of SOP Classes and Transfer Syntaxes [39,42,46]. The integration as presented in Figure 1 focuses on the integration between the AE and the PACS server.…”
Section: Pydicom: Modify and Write Dicom Files With Pythonmentioning
confidence: 99%